1992
DOI: 10.1038/hdy.1992.49
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical homogamy and unequal sex ratio from reciprocal mating-order crosses between Chorthippus parallelus subspecies

Abstract: To study the evolution of this Pyrenean hybrid zone following postglacial secondary contact, a crossing programme was performed involving sequential mating of single females by males of both subspecies in both orders. Progeny were scored as embryos using Acridine orange and C-banding to identify their male parent. This revealed a number of significant departures from straightforward inheritance. There was an excess of pure over hybrid progeny. This homogamy is produced at fertilization but may have been determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 35 publications
(18 reference statements)
3
81
2
Order By: Relevance
“…Fresh sperm is more motile, and more motile sperm has a higher velocity (Aitherton et al 1979) and shows a greater fertilization capacity (Lillie 1919;Roche et al 1968;Lanmann 1968;Miller et al 1969;Lodge et al 1971;Smith & Lodge 1987;Levitan et al 1991;Andre¨& Lindegarth 1995). Bella et al (1992) found slight evidence for sperm ageing in the competitive ability in C. parallelus by comparing the proportion of o¡spring fathered by the second male to mate (P 2 -values) from homogametic and heterogametic matings, but no correlation of sperm age with fertilization success was detected. Although sperm ageing processes and consequences within males and females might be quite di¡erent (Lanmann 1968), there seems to be a similar e¡ect of a decrease in sperm quality aged in the testes of human males.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fresh sperm is more motile, and more motile sperm has a higher velocity (Aitherton et al 1979) and shows a greater fertilization capacity (Lillie 1919;Roche et al 1968;Lanmann 1968;Miller et al 1969;Lodge et al 1971;Smith & Lodge 1987;Levitan et al 1991;Andre¨& Lindegarth 1995). Bella et al (1992) found slight evidence for sperm ageing in the competitive ability in C. parallelus by comparing the proportion of o¡spring fathered by the second male to mate (P 2 -values) from homogametic and heterogametic matings, but no correlation of sperm age with fertilization success was detected. Although sperm ageing processes and consequences within males and females might be quite di¡erent (Lanmann 1968), there seems to be a similar e¡ect of a decrease in sperm quality aged in the testes of human males.…”
Section: Discussionmentioning
confidence: 99%
“…Females of this and related species mate at a maximum of one time per oviposition (Renner 1952;Haskell 1958;Hartmann & Loher 1996; K. Reinhardt and G. KÎhler, unpublished data; but see Bella et al 1992) as they are not receptive between copulation and oviposition (Renner 1952;Hartmann & Loher 1996). They can reject males for more than one oviposition (Haskell 1958;Kriegbaum & Von Helversen 1992;K.…”
Section: (A) General Rearing Conditions and Female Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few exceptions to random gamete fertilization, however, have been reported up to now, especially in animals where sperm success in fertilization seems to depend little or not at all on the genotype (Muller & Settles, 1927;Zimmering et al, 1970). Homogamy caused by preferential fertilization, however, has been reported in a few cases of hybridization between closely related animals (Hewitt et a!., 1987(Hewitt et a!., , 1989Bella et a!., 1992;Gregory & Howard, 1994;Wade et al, 1994). In plants, however, the pollen-tube growth velocity could play a significant role in competition between pollen grains to fertilize the macrospore.…”
Section: Introductionmentioning
confidence: 99%